KVALITATIV METODE I PRAKSIS - Friedman, Kajsa Ekholm (Tidsskriftet Antropologi, 1995)
Kajsa Ekholm Friedman: Qualitative Method in Practice Social anthropologists doing fieldwork must realize that no transformation of „us“ into „hem" is possible. Instead they must rely on communication across cultural horders. By carefully going through informants narratives and statements during interviews. Kajsa Ekholm Friedman illustrates how such dialogues can take place. Her first example is from fieldwork in Congo. It shows how the encounter with a different tradition of sensemaking leads to a situation where no sense can be made at all. Ekholm Friedman then goes on to describe how the fieldworker gradually builds up new understandings. The second example contains some intriguing episodes from fieldwork in Hawaii where Ekholm Friedman explores the Hawaiian practice of adoption, hanai. Here, it is the emphasis on sameness rather than difference between the fieldworker and the informant which is the primary method that leads to understanding. However, in the final part of the Hawaiian interviews we leam how the focus on sameness must never exclude the sensitivity for difference, nor the awareness of dominant actors and their hegemonic interpretations.